Advances in polymer science : 7. band (Berlin ; New York : Springer-Verlag, 1971)
Beginning with 17, each issue contains a cumulative author index.
Includes bibliographical references.
Keywords: Polymers -- Periodicals; Polymerization -- Periodicals